Primary mesenchymal stromal cells in co-culture with leukaemic HL-60 cells are sensitised to cytarabine-induced genotoxicity, while leukaemic cells are protected. (10th September 2021) - Gynn, Liana E; Anderson, Elizabeth; Robinson, Gareth; Wexler, Sarah A; Upstill-Goddard, Gillian; Cox, Christine; May, Jennifer E
Abstract: Tumour microenvironments are hallmarked in many cancer types. In haematological malignancies, bone marrow (BM) mesenchymal stromal cells (MSC) protect malignant cells from drug-induced cytotoxicity. However, less is known about malignant impact on supportive stroma. Notably, it is unknown whether these interactions alter long-term genotoxic damage in either direction. The nucleoside analogue cytarabine (ara-C), common in haematological therapies, remains the most effective agent for acute myeloid leukaemia, yet one-third of patients develop resistance. This study aimed to evaluate the bidirectional effect of MSC and malignant cell co-culture on ara-C genotoxicity modulation. Primary MSC, isolated from patient BM aspirates for haematological investigations, and malignant haematopoietic cells (leukaemic HL-60) were co-cultured using trans-well inserts, prior to treatment with physiological dose ara-C. Co-culture genotoxic effects were assessed by micronucleus and alkaline comet assays. Patient BM cells from chemotherapy-treated patients had reduced ex vivo survival ( P = 0.0049) and increased genotoxicity ( P = 0.3172) than untreated patients. It was shown for the first time that HL-60 were protected by MSC from ara-C-induced genotoxicity, with reduced MN incidence in co-culture as compared to mono-culture ( P = 0.0068). Comet tail intensity also significantly increased in ara-C-treated MSC with HL-60 influence ( P = 0.0308). MSC sensitisation to ara-C genotoxicity was also demonstrated following co-culture with HL60 ( P = 0.0116), which showed significantly greater sensitisation when MSC-HL-60 co-cultures were exposed to ara-C ( P = 0.0409). This study shows for the first time that malignant HSC and MSC bidirectionally modulate genotoxicity, providing grounding for future research identifying mechanisms of altered genotoxicity in leukaemic microenvironments. MSC retain long-term genotoxic and functional damage following chemotherapy exposure. Understanding the interactions perpetuating such damage may inform modifications to reduce therapy-related complications, such as secondary malignancies and BM failure.